Predictions of Daily Horizontal Solar Radiation for Rural Development: The Case of Mubi Town, Adamawa State, Nigeria - Raji, Luqman; Amusat, Ramoni Olawale; Anjorin, Olufemi Jacob; Idris, Mohammed Hassan; Issa, Abdul-jeleel Kehinde (Bandung State Polytechnic (Politeknik Negeri Bandung), 2020)
The solar radiation which is produced by the sun has created interests for the renewable researchers in the area of solar technology to make environment friendly and develop communities through this abundant energy potential. This study developed a model of Daily Horizontal Solar Radiation (DHSR) for Mubi, Adamawa State, Nigeria. The present study data were obtained from National Aeronautics and Space Administration (NASA) in year 2017. The sought data were air temperature and Relative Humidity which were used as the input parameters and DHSR used as output. Mathematical Model of DHSR of the study area was generated through the Multiple Linear Regression (MLR) analysis that was done in the Microsoft World Excel. Results of the research were validated using statistical tools of Mean Square Error and Correlation Coefficient given 1.61 and 0.95 respectively. Consequently, it was concluded that MLR Model can be considered as a substitute for evaluating the Actual DHSR for weather condition data of Mubi. Therefore, this finding is significant to the development of the socio-economic activities of the Mubi Town. Based on this finding it was recommended that the behavious of MLR Model should be tested in other locations across the Northeast, Nigeria.